PENGARUH KEPUASAN KERJA, MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU DI SMAN 1 MANGGELEWA-DOMPU - Weni Armianti; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
abstrackThis study aims to determine the effect of job satisfaction, motivation and organizational commitment to teacher performance. The sample in this study amounted to 47 people who are all teachers at SMAN 1Manggelewa-Dompu.The method used is descriptive data analysis by using the test of validity, reliability, normality, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, t hypothesis test, and hypothesis testing f.The results of this study indicate that the variable job satisfaction has a significant influence on teacher performance motivation variable has no significant influence on teacher performance and organization commitment variable has significant effect on teacher performance in SMAN 1 Manggelewa-Dompu.Keywords: job satisfaction, motivation, organizational commitment, teacher performance